DIFFERENT IMPRESSION MATERIALS USED FOR COMPLETE DENTURE FABRICATION – A REVIEW - Vijaya Kumaran, Ghayathri; Robin, Kirubha; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
There are many impression materials that are used for the fabrication of complete dentures. These materials are used to ensure the quality of the impression obtained and also the techniques used while making the impression. Moreover, the combination of excellent physical properties and its handling features assures the stability of the impression material. This review is to emphasise the availability of different impression materials for complete denture fabrication.